About problems of implementation of it-systems in practical health care - V. A. Lipatov; I. G. Zaytsev; D. A. Severinov (Бюллетень сибирской медицины, 2018)
The article presents the background of healthcare system computerization development starting from the time when preconditions for IT systems implementation appeared up to the present moment. It outlines the problems that emerged in the course of implementing the projects aimed at computerizing the RF Healthcare System and providing a high-technology support for it; it features also the indicators related to financial investments into the healthcare information systems. Based on the reports of the authorized agencies the project implementation efficiency is analyzed and solution options for the existing problems are shown. The article reveals development prospects for IT implementation in healthcare.Objective. Study of IT systems development and incorporation into the practical healthcare structure of the Russian Federation based on the freely available data. Laws and regulations, including reports in healthcare, publications of Russian and foreign lead researchers in economics and medical administration, analytical reviews of consulting companies such as RBC, Price Waterhouse Coopers (London, UK), C-News Analytics (Russia, Moscow), and Vademecum business magazine (Russia, Moscow).Results. The healthcare computerization process in Russia is slower than it is set out in the Governmental plans. The most common and significant problems include the following: lack of funding for the computerization process in general; irrational distribution of resources within the projects and selection of a costly computerization strategy from the beginning; corrupt practices; conflicts between customers with the contractors because of which many projects were not implemented; management problems; a clash between the current legislation to modern technologies and trends, lack of efforts aimed at implementation of healthcare information systems on the part of the regional authorities.Conclusion. To make the healthcare computerization more successful it is required to awaken a commercial interest in the private IT companies to attract additional investment. Personal responsibility of the officials in charge of the computerization should become more stringent in case of a delay in a project or a project failure, the government procurement system should be improved in order to attract the most qualified integrators, the interaction between healthcare managers at various levels with the integrators should be facilitated through reducing bureaucratic «paper» load. At the state level it is necessary to focus on the operational improvement of the RF legislation to ensure the progressive development and implementation of information technologies.